Talking Saivism in a Tamil migrant faith classroom. Issue 3 (3rd July 2022) - Perera, Nirukshi
ABSTRACT: This study is located in a lesser-known educational context and investigates aspects of migration, religion and multilingualism. Focusing on the discourse of second-generation adolescent migrants in a Tamil Hindu temple school in urban Australia, I discuss how flexible language practices manifest in this migrant faith setting. I argue that the use of the heritage language is not always at the forefront, despite a monolingual Tamil language policy, because religious transmission is given priority over language transmission. At the same time, there are certain motivations that influence the use of Tamil: to index the close relationship between language and religious culture and to index one's membership of the ethnoreligious community. This paper draws on ethnographic data to provide both a macro and micro view of these motivations – what drives adolescents to use their heritage language, how it is deployed from their linguistic repertoires, and how it contrasts with the use of the students' dominant language, English. The analysis takes a whole of conversation approach to understanding the relationship between religion and heritage language use for second-generation migrant students.